2021
DOI: 10.1186/s12711-021-00653-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection for environmental variance of litter size in rabbits involves genes in pathways controlling animal resilience

Abstract: Background Environmental variance (VE) is partially under genetic control, which means that the VE of individuals that share the same environment can differ because they have different genotypes. Previously, a divergent selection experiment for VE of litter size (LS) during 13 generations in rabbit yielded a successful response and revealed differences in resilience between the divergent lines. The aim of the current study was to identify signatures of selection in these divergent lines to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…This might suggest again that fancy rabbit breeds should be considered apart from other rabbit lines where inbreeding is usually avoided to maintain high production performances. Runs of homozygosity were also investigated in rabbits by Casto-Rebollo et al (2021) for another purpose. These authors used ROH to identify signatures of divergent selection in a rabbit population from which divergent lines for environmental variance of litter size were established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might suggest again that fancy rabbit breeds should be considered apart from other rabbit lines where inbreeding is usually avoided to maintain high production performances. Runs of homozygosity were also investigated in rabbits by Casto-Rebollo et al (2021) for another purpose. These authors used ROH to identify signatures of divergent selection in a rabbit population from which divergent lines for environmental variance of litter size were established.…”
Section: Discussionmentioning
confidence: 99%
“…Runs of homozygosity were also investigated in rabbits by Casto‐Rebollo et al ( 2021 ) for another purpose. These authors used ROH to identify signatures of divergent selection in a rabbit population from which divergent lines for environmental variance of litter size were established.…”
Section: Discussionmentioning
confidence: 99%
“…These are directly related to higher profitability and improvement in animal welfare (Bolet et al, 2007;Poigner et al, 2000). Recently, Casto-Rebollo et al (2021) have shown that selection to modify the environmental variance of litter size involve genes with a functional mutation in their transcription units and are mostly implicated in the immune response and stress response pathways. More uniform animals would be less affected by unappreciable environments environment changes thus keeping their performance, which is a sign of robustness.…”
Section: Introductionmentioning
confidence: 99%
“…One of the powerful tools to sustain livestock production to feed the rapidly developing populations is to enhance their reproductive potential (Roszkos et al, 2020). Rabbit does can give birth to two to nine kittens in each pregnancy (Casto-Rebollo et al, 2021); therefore, the high reproductive rate of rabbits could provide animal protein source to feed the growing human populations. Nutrition plays a crucial role in reproduction (Attia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%